Performance analysis of some improved lines of Leucaena leucocephala and Leucaena hybrids - Gupta, S.K.; Gupta, V.K. (Indian Journal of Agroforestry, 2020)
One selection S24, two interspecific hybrids KX1 and KX2 of Leucaena leucocephala x L. diversifolia were evaluated alongwith two checks (K8 and K636) for 4.5 years in a randomized block design for growth and production traits in degraded and rocky soil. Based on mean productivity, selection S24 ranked first with average productivity of 16.23 t ha-1 yr-1 followed by K636 (12.33 t ha-1 yr-1) and KX3(1 0.68 t ha-1 yr-1). Percent superiority of S24 over K8 for mean productivity was 64%.